A new elasmosaurid plesiosaurian from the Early Cretaceous of Russia marks an early attempt at neck elongation. Issue 4 (16th October 2020) - Fischer, Valentin; Zverkov, Nikolay G; Arkhangelsky, Maxim S; Stenshin, Ilya M; Blagovetshensky, Ivan V; Uspensky, Gleb N
Abstract: Plesiosaurian marine reptiles evolved a wide range of body shapes during the Jurassic and Cretaceous, including long-necked forms. Many Late Cretaceous members of the clade Elasmosauridae epitomized this part of the plesiosaurian morphological spectrum by evolving extremely long necks through somitogenesis (resulting in an increase in the number of cervical centra) and differential growth (resulting in the elongation of cervical centra). However, the early evolution of elasmosaurids remains poorly understood because of a generally poor Lower Cretaceous fossil record. We describe a new elasmosaurid, Jucha squalea gen. et sp. nov., from the upper Hauterivian (Lower Cretaceous) of Ulyanovsk (European Russia), in addition to other elasmosaurid remains from the same area. Jucha squalea is one of the oldest and basalmost elasmosaurids known and lacks a series of features that otherwise characterize the group, such as the heart-shaped intercoracoid fenestra and the median pectoral bar. However, Jucha squalea marks an early attempt at cervical elongation through differential growth. The data we gathered on the shape of cervical centra among elasmosaurids suggest multiple episodes of elongation and shortening. However, the precise patterns are obscured by an unstable phylogenetic signal.